FRI0565 A MULTINATIONAL STUDY OF THROMBOTIC MICROANGIOPATHY IN MACROPHAGE ACTIVATION SYNDROME: A DREADFUL CONDITION WHICH IS LIKELY UNDER-RECOGNIZED. (June 2019) - Minoia, Francesca; Tibaldi, Jessica; Muratore, Valentina; Gallizzi, Romina; Bracaglia, Claudia; Arduini, Alessia; Çomak, Elif; Vougiouka, Olga; Trauzeddel, Ralf; Filocamo, Giovanni; Micalizzi, Concetta; Ravelli, Angelo; et al.
Abstract : Background: Macrophage activation syndrome (MAS) is a severe complication of rheumatologic conditions, mainly systemic juvenile idiopathic arthritis (sJIA), and is classified as a secondary form of hemophagocytic lymphohistiocytosis (HLH). Thrombotic microangiopathy (TMA) is a heterogeneous group of potentially fatal diseases characterized by microangiopathic hemolytic anemia, thrombocytopenia and organ injury. The association between TMA and HLH has been described only in single reports in renal transplant recipients 1 and in two cases of virus-induced HLH 2 . TMA associated with MAS has never been reported so far Objectives: To present the preliminary data from a multinational cohort of pediatric patients with MAS and TMA Methods: The clinical charts of patients with MAS were retrospectively reviewed to identify the instances that were associated with TMA. Demographic, clinical and laboratory features at MAS and TMA onset, therapeutic interventions and outcome were collected. Results: A total of 14 patients, 71.4% females, with MAS and TMA were collected. An underlying rheumatologic disease was reported in 9/14 (8 sJIA or sJIA-like illness and 1 systemic lupus erythematosus). The median age at MAS onset was 8.6 years. In 5 patients MAS and TMA occurred simultaneously, whereas in 4 TMA preceded and in 5 followed MAS. The main features at MAS and TMA onset are presented in Table. Low complement levels and reduced ADAMTS13 activity were observed in 75% and 43% of patients respectively. For MAS management, 85.7% of patients received high-dose corticosteroids and 71.4% cyclosporine; in 5 cases anakinra was added. TMA episodes were treated with plasma-exchange in 57.1% of patients; 7 patients were given biologics (1 rituximab and 6 eculizumab) with good results. Admission to the Intensive Care Unit was required in 85.7% of cases. All patients survived. Conclusion: The association of MAS and TMA is a life-threatening condition, likely under-recognized. Clues to suspect TMA in a patient with MAS are the increase in LDH and decrease in platelet count out of proportion of other laboratory abnormalities, the drop in haptoglobin level, the finding of schistocytes in blood smear and the new onset of hematuria. Biologics, particularly rituximab and eculizumab, may offer an adjunctive therapeutic option for refractory cases. References: [1] Esmaili H, et al. An update on renal involvement in hemophagocytic syndrome. J Nephropathol 2016; 2Fraga-Rodriguez GM, et al. Eculizumab in a child with atypical haemolytic uraemic syndrome and haemophagocytic lymphohistiocytosis triggered by cytomegalovirus infection. BMJ Case Rep2017. Disclosure of Interests: Francesca Minoia: None declared, Jessica Tibaldi: None declared, Valentina Muratore: None declared, Romina Gallizzi: None declared, Claudia Bracaglia: None declared, Alessia Arduini: None declared, Elif Çomak: None declared, Olga Vougiouka: None declared, Ralf Trauzeddel : None declared, Giovanni Filocamo: None declared, Concetta Micalizzi: None declared, Angelo Ravelli Grant/research support from: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Consultant for: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche, Speakers bureau: Angelini, AbbVie, Bristol-Myers Squibb, Johnson & Johnson, Novartis, Pfizer, Reckitt Benkiser, and Roche